Effect of Ultrasonic Treatment on Transformations of Arsenic Species in Edible Mushrooms. (2nd January 2020) - Chen, Shuangyang; Kimatu, Benard Muinde; Fang, Donglu; Chen, Xin; Chen, Guitang; Hu, Qiuhui; Zhao, Liyan
Abstract: A study on the transformations of six arsenic species (arsenocholine (AsC), arsenobetaine (AsB), dimethylarsinic acid (DMA), monomethylarsonic acid (MMA), arsenite (As(III)), and arsenate (As(V))) was carried out in aqueous solution by ultrasonic treatment. The transformations of arsenic species increased with time. As the ultrasonic power or temperature was increased, transformations of arsenic species were at first enhanced and then decreased. AsC, AsB, As(III) were the most unstable at 600 W and 20 °C. DMA and MMA were stable; AsC was partially transformed to AsB, trimethylarsinic oxide (TMAO), and the more toxic tetramethylarsonium ion (TMA + ); AsB was partially transformed to TMAO; and As(III) was easily oxidized to As(V). The reduction of As(V) to As(III) was only observed when the temperature was over 60 °C. The ultrasound treatment conditions with relatively stable arsenic species were 150 to 300 W, 40 to 80 °C, and 0 to 10 min. The relatively stable (150 W, 10 min, 80 °C) and unstable (600 W, 60 min, 20 °C) ultrasonic condition were applied to mushrooms and the transformations of AsC, AsB, and As(III) were observed. Currently, ultrasound-assisted extraction methods have only focused on the extraction efficiency of arsenic species and ignored their transformations. This study may serve as a guide for improving extraction efficiency without minimal transformation of the arsenic forms to reflect the actual contents in edible mushrooms. The study also provides a theoretical basis for making an accurate risk evaluation of human exposure by taking account of possible arsenic transformations during processing prior to consumption.